Desain Instruksional Pembelajaran Matematika Pada Materi Bangun Ruang Untuk Siswa Kelas VII SMP - Amarta Prayuti; Tian Abdul Aziz; Flavia Aurelia Hidaja; Lukman El Hakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the world of education, instructional design development is important to do in order to create improvements in the teaching and learning process. The purpose of this study is to provide an overview of instructional design design in learning mathematics in class VII junior high school building materials. The research method used is Systematic Literature Review using several article reviews indexed by Sinta and Scopus. The search for article reviews was carried out on several platforms including google scholar and eric. The results showed that the learning design used the Problem-based Learning model with the Teaching at the Right Level approach with the help of technology and several assessment instruments. Further details of the learning design are explained in detail in the results and discussion section of this article.